Influence of typical drivers' unsafe driving behaviors to traffic operation: An exploratory study in Kunming, China. (September 2017) - Hu, Liwei; Xue, Gang; Wang, Miao; Chen, Zheng; Zhang, Ting; Li, Linyu; Qin, Lihui
This article obtains the impact data of drivers' unsafe driving behaviors to urban traffic flow through spot field investigation, questionnaires, and traffic accidents dossier. The influence of drivers' unsafe driving behaviors (driving on the road markings, short following distance, being forced to change lanes, and illegal parking) to the vehicle speed is analyzed, and the impact descending order (illegal parking, being forced to change lanes, driving on the road markings, and the last is short following distance) of the four typical unsafe driving behaviors to the vehicle speed is obtained. At the same time, the impact descending order (being forced to change lanes, short following distance, illegal parking, and the last is driving on the road markings) of the four typical drivers' unsafe driving behaviors to the traffic flow density is obtained. Some of the unsafe situation which is caused by the drivers' unsafe driving behaviors is analyzed, such as the lane suddenly narrowing but the number of lanes does not change, reducing the number of lanes, and lane exit confusion. According to these, the basic road traffic capacity is corrected under the road condition of drivers' unsafe driving behaviors. The research results provide a theoretical basis for improving the relevant laws and regulations, which has an important theoretical and practical value on improving the transportation efficiency and the safety standards of the road traffic system.